2018
DOI: 10.1007/s40415-018-0507-3
|View full text |Cite
|
Sign up to set email alerts
|

Genome survey and development of 15 microsatellite molecular markers in Syagrus coronata (Martius) Beccari (Arecaceae) by next-generation sequencing

Abstract: Syagrus coronata (Martius) Beccari belongs to the Arecaceae family, an economically and ecologically important species of palm tree. It grows in northeastern Brazil and has a widespread geographic distribution in the ''Caatinga'' (a seasonally dry tropical forest biome) and Atlantic forest domains (a rain forest biome). The aim of this study was to perform a genome survey and develop SSR markers using high-throughput sequencing. We obtained 78,231,881 million Illumina single-end and paired-end reads, and these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…When subjected to the PCR, all primers were ampli ed, with primers Cop02, Cop07, Cop10 and Cop15 presenting the best ampli cation results. Barbosa and Almeida (2018), working with Syagrus coronata (Martius) Beccari, selected temperatures between 58 to 60 ºC. This variation is probably because different genera respond differently to temperature variation.…”
Section: Resultsmentioning
confidence: 99%
“…When subjected to the PCR, all primers were ampli ed, with primers Cop02, Cop07, Cop10 and Cop15 presenting the best ampli cation results. Barbosa and Almeida (2018), working with Syagrus coronata (Martius) Beccari, selected temperatures between 58 to 60 ºC. This variation is probably because different genera respond differently to temperature variation.…”
Section: Resultsmentioning
confidence: 99%
“…Other studies using microsatellites confirmed the prevalence of inbreeding in Acrocomia aculeata populations, product of crosses between very close relatives, or even full siblings [ 46 , 47 , 48 ]. For Syagrus coronata , for example, the authors take into account the high-level of inbreeding to conduct conservation measures [ 49 ]. Given that the sclerophyllous forest inhabited by J. chilensis has been highly exploited and approximately only 121,284 specimens are found in Central Chile (2.5% of the original population of the 19th century), being distributed among highly fragmented populations [ 26 , 50 , 51 ], conservation measures for this species should consider the low level of genetic diversity and inbreeding found in our study.…”
Section: Discussionmentioning
confidence: 99%
“…A large number of genome-wide SSR loci have provided a foundation for the further construction of high-density genetic maps and the study of the regulatory mechanisms of medicinal ingredients derived from I. chinensis [ 14 , 43 , 44 ]. For most plants, the di- and trinucleotide repeat motif types mostly contribute to the major proportion of SSRs, and a notably small proportion was contributed by tetra-, penta-, and hexanucleotide repeat motif types [ 15 , 33 , 45 , 46 ]. In this study, the mononucleotide repeat was the most abundant type, which was similar to many species, such as Sillago sihama [ 47 ], Betula platyphylla [ 46 ], and R. micranthum [ 14 ].…”
Section: Discussionmentioning
confidence: 99%